Mykobiota krzewów jałowca Juniperus x media z objawami zamierania na terenie oczyszczalni ścieków w Poznaniu - Behnke-Borowczyk, Jolanta; Kwaśna, Hanna; Szewczyk, Wojciech; Zatorski, Jacek (Leśne Prace Badawcze, 2019)
The frequency and diversity of fungi in branches, roots and soil was examined in 3–10-years-old diseased Juniperus x media trees growing in the surroundings of the sewage treatment facility in Poznań. Symptoms of branch dieback appeared first on the older parts inside the crown and mostly in the lower part of trees subsequently spreading upwards and outwards. Our analyses included extraction of environmental rDNA from branches, roots and soil, amplification of the rDNA with fungi specific primers and sequencing. Fungal taxa from Ascomycota, Basidiomycota, Chytridiomycota, Glomeromycota and Zygomycota were detected with a total of 695, 135 and 196 taxa in branches, roots and soil, respectively. Fungal communities included plant pathogens, opportunistic pathogens, epiphytes or endophytes, mycorrhizal taxa, saprotrophs common on organic debris and in soil, human and animal pathogens, entomopathogenic taxa, mycoparasites, white and black yeasts, taxa with antagonistic and medicinal properties and lichenized fungi. The frequency of potential plant pathogens was 2.64–33.12% in branches, 0.88% in roots and 1.29–2.93% in soil. The most common pathogens were species from Chalara, Cytospora, Fusarium, Ilyonectria, Mycosphaerella, Setomelanomma (Ascomycota) and Armillaria, Rhizoctonia (Basidiomycota) genera. The less frequent pathogens included species from Leptosphaeria , Lophodermium and Septoria genera. In conclusion, oxygen deficiency and the presence of poisonous gases in the air around the sewage plant is likely to have had damaging effects on plants infected or colonized by opportunistic and facultative parasites.